Tinjauan Kasasi Penuntut Umum Atas Dasar Kesalahan Penerapan Hukum Judex Factie Dalam Perkara Lingkungan Hidup - Aminatul Malihah (Sebelas Maret University, 2017)
This research aims to determine the suitability of the reasons Cassation from Public Prosecutor based on Judex Factie (Court of Appeal) misapplied the law or enforce the rule of law is not as it should in the case of the environment with the provision of Article 253 paragraph (1) KUHAP juncto Article 116 paragraph (1) letter a of Law Number 32 Year 2009 on Protection and Management Environment. The reason Cassation from Public Prosecutor first is Judex Factie misapplied the Law Number 40 Year 2007 on Limited Company,which Judex factie only consider Article 98 paragraph (1) which states that “The Board of Directors to represent the Company both in and out of court”, without considering Article 103 which states that “The Board of Directors may authorize employees and the liability on behalf of the Company to take legal actions”. Case with defendant PT Karawang Prima Sejahtera Steel (PT KPSS), both the Directors and Commissioners were in China, so PT KPSS was led and managed by Wang Dong Bing as the Chief of General. The second reason Cassation from Public Prosecutor was in the indictment Public Prosecutor indicted PT KPSS as a Corporation which represented by Wang Dong Bing as the Chief of General, not Wang Dong Bing as a person, but the verdict in High Court Bandung Number 170/Pid.Sus/2012/PT.Bdg liberated Wang Dong Bing from the indictment Public Prosecutor. Both reasons Cassation justified by Judex Juris, so there is a suitability between the reason Cassation from Public Prosecutor with the provision of article 253 paragraph (1) KUHAP juncto Article 116 paragraph (1) letter a Law Number 32 Year 2009 on the Protection and Management Environment. Keyword: Cassation, Corporation, Environmental Crime This research aims to determine the suitability of the reasons Cassation from Public Prosecutor based on Judex Factie (Court of Appeal) misapplied the law or enforce the rule of law is not as it should in the case of the environment with the provision of Article 253 paragraph (1) KUHAP juncto Article 116 paragraph (1) letter a of Law Number 32 Year 2009 on Protection and Management Environment. The reason Cassation from Public Prosecutor first is Judex Factie misapplied the Law Number 40 Year 2007 on Limited Company, which Judex factie only consider Article 98 paragraph (1) which states that “The Board of Directors to represent the Company both in and out of court”, without considering Article 103 which states that “The Board of Directors may authorize employees and the liability on behalf of the Company to take legal actions”. Case with defendant PT Karawang Prima Sejahtera Steel (PT KPSS), both the Directors and Commissioners were in China, so PT KPSS was led and managed by Wang Dong Bing as the Chief of General. The second reason Cassation from Public Prosecutor was in the indictment Public Prosecutor indicted PT KPSS as a Corporation which represented by Wang Dong Bing as the Chief of General, not Wang Dong Bing as a person, but the verdict in High Court Bandung Number 170/Pid.Sus/2012/PT.Bdg liberated Wang Dong Bing fromthe indictment Public Prosecutor. Both reasons Cassation justified by Judex Juris, so there is a suitability between the reason Cassation from Public Prosecutor with the provision of article 253 paragraph (1) KUHAP juncto Article 116 paragraph (1) letter a Law Number 32 Year 2009 on the Protection and Management Environment. Keyword: Cassation, Corporation, Environmental Crime